Hereditary Cancer Syndromes - Rahner, Nils (Deutscher Arzte Verlag, 2008)
INTRODUCTION: Persons carrying mutations for hereditary cancer syndromes are at high risk for the development of tumors at an early age, as well as the synchronous or metachronous development of multiple tumors of the corresponding tumor spectrum. The genetic causes of many hereditary cancer syndromes have already been identified. About 5% of all cancers are part of a hereditary cancer syndrome. METHODS: Selective literature review, including evidence-based guidelines and recommendations. RESULTS: Clinical criteria are currently available according to which many hereditary cancer syndromes can be diagnosed or suspected and which point the way to further molecular genetic analysis. A physician can easily determine whether these criteria are met by directed questioning about the patient’s personal and family medical history. The identification of the causative germ line mutation in the family allows confirmation of the diagnosis in the affected individual and opens up the option of predictive testing in healthy relatives. DISCUSSION: Mutation carriers for hereditary cancer syndromes need long-term medical surveillance in a specialized center. It is important that these persons should be identified in the primary care setting and then referred for genetic counseling if molecular genetic testing is to be performed in a targeted, rational manner.